Prevalence and Measurement of Anxiety in Samples of Patients With Heart Failure: Meta-analysis. Issue 4 (July 2016) - Easton, Katherine; Coventry, Peter; Lovell, Karina; Carter, Lesley-Anne; Deaton, Christi
Abstract : Objectives: Rates of anxiety in patients with heart failure (HF) vary widely, and not all assessment instruments used in this patient population are appropriate. It is timely to consolidate the evidence base and establish the prevalence and variance of anxiety in HF samples. Methods: A systematic review, meta-analysis, and meta-regression were conducted to identify the prevalence, variance, and measurement of anxiety in patients with HF. Results: A total of 14, 367 citations were identified, with 73 studies meeting inclusion criteria. A random effects pooled prevalence of 13.1% (95% confidence interval [CI], 9.25%–16.86%) for anxiety disorders, 28.79% (95% CI, 23.30%–34.29) for probable clinically significant anxiety, and 55.5% (95% CI, 48.08%–62.83%) for elevated symptoms of anxiety was identified. Rates of anxiety were highest when measured using the Brief Symptom Scale-Anxiety scale (72.3%) and lowest when measured using the Generalised Anxiety Disorder-7 (6.3%). Conclusion: Many patients with HF would benefit if screened for anxiety and treated. The conceptualization and measurement of anxiety accounted for most variance in prevalence rates. The Generalised Anxiety Disorder-7 or the Hospital Anxiety and Depression Scale appear to be the most appropriate instruments for this clinical population, with evidence to suggest they can discriminate between depression and anxiety, omit somatic items that may contaminate identification of anxiety in a population with physical comorbidities, and provide thresholds with which to differentiate patients and target treatments. Although there are limitations with the collation of diverse measurement methods, the current review provides researchers and clinicians with a more granular knowledge of prevalence estimates of anxiety in a population of HF patients.